CRIMINAL OFFENSE OF ENVIRONMENTAL POLLUTION IN THE CRIMINAL LEGISLATION OF THE REPUBLIC OF SERBIA AND THE REPUBLIC OF CROATIA - Branislav Babić; Marija Stanković (Pravo, 2023)
Undoubtedly, one of the leading movements at the global level in the past few decades was the movement for the global and intensive protection of the human environment, that is, the affirmation of the right of man to a healthy environment, as a distinct right. Bearing in mind the importance of a healthy environment and the importance of its protection, which has grown from a social need into a legal imperative, it is certainly justified to establish the environment as an independent and primary collective object of protection within the domestic criminal legislation. Taking into account the tendencies on the international and comparative level regarding the regulation of the criminal law protection of the environment, the domestic legislator dedicates an entire chapter of the Criminal Code precisely to incriminations that have the environment as an object of protection, in various forms. As the first offense provided for in Chapter 24 i.e., Criminal offenses against the environment, the legislator defines the general and most significant criminal offense from the group of criminal offenses against the environment, namely, Environmental pollution. This paper is dedicated to the analysis of this criminal offense in domestic criminal legislation, with reference to individual solutions contained in the legislation of the Republic of Croatia and pointing out their differences.